Pencarian Dokumen Skripsi menggunakan BM25 dan Faceted Search berdasarkan Kata Kunci Abstrak (Studi Kasus: Universitas Muhammadiyah Sidoarjo) - Mohammad Fahmi Ilmi; Putra Pandu Adikara; Indriati Indriati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
A thesis is a graduation requirement for students to complete their studies. However, along with the much research that students have carried out, many universities are not ready to provide a forum that can make it easier for students to access the required thesis files, one of which is the Muhammadiyah University of Sidoarjo. To overcome this problem, the researchers developed a program that focuses on finding the thesis document with the help of Information Retrieval. Information Retrieval can help sort out which thesis data is appropriate and will group it into data groups given to seekers. As an improvement, this program is also given an additional feature in the form of category grouping, which is done using Faceted Search based on the keywords of each document. In this research, the BM25 method is used to prove whether this method can produce good accuracy in searching for student thesis data. The tests carried out on 25 queries resulted in the most considerable average value at the value of k=5, with a value of 0.928. This shows that the search results for the most relevant documents are collected in the top 5 documents.